Mobile applications development on the Google Android phone 1 - Chai, Chun Kiat (2013)
Commuters who travel by taxi will have to come across the current in place system for booking of taxi. The current booking system of taxi has some potential flaw and lacks some of the features that commuters want. Most of these features can be implemented through application for smart phones and mobile devices of these days. Features like accurately determine the location of the incoming taxi, flagging taxi that is outside commuters’ visual or accurately and easily convey commuters’ location though visual display in mobile devices. As a result of these features demand, an Android application can be developed to address the above issues and wants. Usage of location services to determine location of both drivers and passengers, usage of a map to visually convey the location of both drivers and passengers, and the internet communication capability of mobile devices to complete and implement the flow as required for the features demanded. Visual display for the location of the users will be from the usage of the mature, free virtual map, Google Maps for Android. Coupled with features and services in Android OS mobile devices, the application Taxickr is developed with a server and database to store and convey information to users for taxi booking purpose. Taxickr will utilise features in Android OS, such as GCM service, web communication to optimise the performance of the application.